SECURITY MANAGEMENT IN PREVENTING POST-EARTHQUAKE SECURITY DISORDERS IN CIANJUR CLASS IIB COMMUNITY INSTITUTIONS - Armani, Muhammad Faisal; Yuska, Syahrial (Journal of Management Small and Medium Enterprises (SMEs), 2025)
This study evaluates security management in preventing security disruptions after an earthquake at Class IIB Cianjur Correctional Facility. The November 2022 earthquake damaged the facility's infrastructure, increasing risks such as inmate escapes, riots, and contraband smuggling. Using a qualitative method, the research found that strict surveillance, patrols, access restrictions, and technology such as CCTV effectively prevented disruptions. However, challenges like staff shortages and coordination during renovation hindered optimal oversight. Overall, security management responded well, though improvements are still needed. Keywords: Security Management; Safety; Earthquake; Correctional Facility